PENGARUH BEBAN KERJA DAN KONFLIK PERAN GANDA TERHADAP TINGKAT STRES KERJA GURU SD SEKECAMATAN TANJUNG MEDAN KABUPATEN ROKAN HILIR - Panji Tuah Jaya; Mahdum Mahdum; Hadriana Hadriana (STKIP Pesisir Selatan, 2022)
This study aims to determine the effect of variables (1) workload on teacher work stress levels, (2) dual role conflict on teacher work stress levels, (3) workload and dual role conflict together on teacher work stress levels. The research respondents were principals of public elementary schools in Tanjung Medan District, Rokan Hilir Regency, totaling 148 people with a sample of 108. The data was collected through the distribution of questionnaires as research instruments. The data analysis used is descriptive analysis and inferential statistical analysis. The instrument reliability coefficient was calculated using the Cronbach alpha formula. The results showed that there was a positive and significant effect of workload on the teacher's work stress level of 0.517, there was a positive and significant influence of dual role conflict on the teacher's work stress level of 0.458. Meanwhile, together there is an effect of workload and dual role conflict on the teacher's work stress level of 0.543